PELAKSANAAN SENAM HAMIL DALAM PENINGKATAN KUALITAS TIDUR PADA IBU HAMIL TRIMESTER III DI PUSKESMAS TALUN KENAS - Megawati Sinambela; Herri Novita Tarigan (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Pregnancy is a change in physiology that is special for a woman as a prospective mother and is also a dream for every married couple. The birth of a baby in a healthy and perfect condition is a hope in every pregnancy process, where this hope can be fulfilled if the baby is born with sufficient body weight. The purpose of this study was to improve the quality of sleep in third Trimester pregnant women, especially at the Talun Kenas Public Health Center, Deli Serdang Regency. The conclusion of the implementation of pregnancy exercise on improving the quality of sleep in third Trimester pregnant women at the Talun Kenas Public Health Center is that pregnancy exercise is very useful for pregnant women because it can also increase the mother's fitness to prepare for childbirth. The number of participants in the implementation of pregnancy exercise was 18 people at the Talun Kenas Public Health Center. After the implementation of the activity there was an increase in the mother's ability to carry out pregnancy exercises independently.